A Nomogram for Predicting Liver Metastasis of Lymph-Node Positive Luminal B HER2 Negative Subtype Breast Cancer by Analyzing the Clinicopathological Characteristics of Patients with Breast Cancer - Yuhan Yue MD; Junqing Liang MD; Yuruo Wu MS; Weibing Tong MD; Dan Li MD; Xuchen Cao MD; Xin Wang MD (Technology in Cancer Research & Treatment, 2022)
Background: Luminal B-like human epidermal growth factor receptor 2 negative (Luminal B [HER2−]) is the most common molecular subtype of breast cancer (BC). Since the relationship between Luminal B (HER2−) BC and liver metastasis (LM) is poorly defined, this retrospective study aimed to develop an LM risk nomogram for patients with lymph node-related (N + Luminal B [HER2−]) BC. Methods: Data were obtained for patients initially diagnosed with BC from the Tianjin Medical University Cancer Institute and Hospital. There were 30,975 Chinese female patients with stage I–III BC and follow-up confirming 1217 subsequent patients with LM, and 427 patients with N + Luminal B (HER2−). The LM risk was assessed using Cox proportional hazards regression, histogram, Venn diagram, and Kaplan–Meier survival analysis, with further analysis for patients with N + Luminal B (HER2−) BC. A nomogram was established based on the N + Luminal B (HER2−) BC data, which was validated using calibration plots. Results: The median age of 427 patients with N + Luminal B (HER2−) liver metastasis of breast cancer (BCLM) was 49 years. The largest number of patients with BCLM was diagnosed between the second to the 6th year, the longest interval from initial BC diagnosis to subsequent LM was 145 months. The patients with LM as the first site of distant metastasis which is associated with better survival were analyzed by Kaplan–Meier. The nomogram was constructed for the risk of LM that included age, menstrual status, unilateral oophorectomy, pregnancy, hepatitis B antigen, region of residence, tumor size, lymph node, clavicular lymph nodes, progesterone receptor, and lymph vessel invasion. Conclusion: We described the clinicopathological characteristics of patients with stage I–III BC, and constructed a nomogram for calculating personalized LM probabilities for patients with N + Luminal B (HER2−), which could guide future prolonged or early extensive treatment decisions.